Race influences the relationship between aerobic power and heart rate recovery - Esco, M. R.; Williford, H. N. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: This investigation examined the association between aerobic fitness, race, and heart rate recovery. Methods: Forty white and 40 black subjects participated in the study and were group matched based on age and maximal oxygen consumption (VO2max) which was determined via a maximal graded exercise test on a treadmill. Heart rate recovery was evaluated at 1-minute (HRR1) and at 2-minutes (HRR2) during an active cool-down period. The subjects were divided by race and whether they were above (A) or below (B) the referenced 50th percentile for VO2max for men age 20 - 29 years. Results: When evaluating each race separately, the white men who were in the A group had significantly faster HRR1 (18.2 ± 5.9 beats/min in A versus 16.7 ± 6.0 beats/min in B) and HRR2 (40.9 ± 10.3 beats/min in A versus 32.1 ± 8.5 beats/min in B) compared to the white men in the B group. However, there was no significant difference in either HRR1 (18.2 ±5.9 beats/min in A versus 16.7±6 beats/min in B) or HRR2 (43.1±10.3 beats/min in A versus 44.4.6±8.2 beats/min in B) between the A and B groups in the black men. The only significant correlation existed between VO2max and HRR2 in the white subjects (r=0.33, P) Conclusion: The results of this study suggest that HRR is associated with aerobic fitness in white men but not in black men.